The return of public media policy in New Zealand: New hope or lost cause?. (1st March 2019) - Thompson, Peter A.
The formation of a new coalition government in New Zealand in the wake of the 2017 election ended three terms of National-led governments and raised the prospect of a significant shift in media policy. National had insisted that in the digital media ecology, the funding of public broadcasting institutions was no longer a priority and that platform-neutral contestable funding of local content would ensure the quality and diversity of content. This saw the demise of the TVNZ Charter and its two commercial-free channels (TVNZ 6 and 7), while both Radio New Zealand (RNZ) and the local content funding agency, NZ On Air, had their funding frozen. The 2017 election of the Labour-NZ First-Green government came with the promise of an additional investment of NZ$38m in public media, the expansion of RNZ's remit to include a commercial-free television channel, and the establishment of an independent commission to assess funding needs for public media. However, the media ecology Labour now faces entails new policy complexities. Deregulation, financialization and convergence have not only intensified commercial pressures on the media, they have led to important shifts in the ways audiences discover and engage with media content. In turn, this complicates the traditional models of state intervention intended to deliver public service outcomes. Adopting a critical institutionalist framework this article will highlight key shifts in media policy trajectory since 1999 and highlight some key differences between the public broadcasting initiatives of 1999‐2008 and the approach thus far of the incoming government. The article analyses how competing intra-party and inter-ministerial priorities have circumscribed the media policy options available and thereby highlight the way political‐economic interests in the media ecology manifest in public policy.